Grain Yield Stability Analysis of Lentil Genotypes by AMMI Indices - Payam Pezeshkpour; Reza Amiri; Iraj Karami; Amir Mirzaei (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: Due to the presence of nitrogen-fixing bacteria in its roots, the lentil plant causes biological nitrogen fixation, and in addition to meeting the plant's need for this substance, they also add some pure nitrogen to the soil each year. Therefore, it has made the soil fertile, especially in dry areas, and in this sense, it is considered a suitable rotation for rainfed cereals. Lentils are a significant source of food proteins, minerals (potassium, phosphorus, iron, and zinc), carbohydrates, and vitamins in human nutrition and have high health benefits due to their low fat content and glycemic index. The low yield of lentil genotypes is caused by various factors, including poor soil fertility, lack of high-yielding improved cultivars, severe moisture stress, diseases, pests, weeds, and inadequate crop management skills. In recent years, global climate change, especially due to rainfall and environmental changes, has significantly impacted lentil production. In Iran, lentils are usually cultivated in spring under rainfed conditions while autumn cultivation increases grain yield due to increasing rainfall efficiency compared to spring cultivation under rainfed conditions. In addition, to maximize yield and control phenotypic expression, breeders must select specific genotypes that are stable or adapted to a specific environment. Therefore, the identification of high-yield genotypes with adaptation to a wide range of environments is one of the major goals in crop breeding programs. In multi-environment experiments, lentil yield is influenced by the genetic structure, environment, and genotype × environment interaction. To better interpret the genotype × environment interaction, the additive main effects and multiplicative interaction (AMMI) model is one of the most common methods in the study of multi-environment experiments. The current study aimed to investigate the genotype ×environment interaction effect on lentil genotypes and to identify stable, high-yielding genotypes compatible with the climatic conditions of temperate rainfed regions in Iran. Methods: In this study, 12 promising lentil genotypes along with “local”, “Kimia”, and “Gachsaran” cultivars were cultivated in a randomized complete block design for three consecutive cropping years (2019-2022) in Lorestan/Khoramabad, Ilam/Chardavel, and Kermanshah/Sararood. In the field, each plot consisted of 4 m planting rows with a distance of 25 cm and a density of 200 seeds per square meter. Stability analysis was performed using the AMMI multivariate method. Statistical analyses were performed using Metan and GGE packages of multi-environment experiments in R software. Results: The AMMI analysis of variance showed the significant effects of the environment, genotype, the genotype × environment, and the first seven main components. Therefore, the significance of genotype × environment interaction allows for the stability analysis of these data. According to AMMI analysis, the first and second main components of the genotype-environment interaction accounted for 45.6 and 19% of genotype × environment interaction variations, respectively. The effect of the first seven main components was significant and in total explained 99.5% of the variations of genotype × environment interaction. The shares of the environment, genotype, and interaction of genotype × environment in the sum of total squares were 54.56, 5.45, and 16.9%, respectively. Among the studied genotypes, the highest grain yield belonged to Genotype 10 with 850 kg/ha, followed by Genotypes 12, 6, and 4. Based on the ASV stability index, genotypes 3, 5, and 1, based on the SIPC index, genotypes 3, 1, 7, and 10, based on the EV index, genotypes 1, 10, and 3, and based on Za and WAAS indexes, genotypes 3, 1, 5, and 10 were the most stable genotypes. Based on the simultaneous selection index of ssiASV, genotypes 10, 4, 5, and 1, based on the ssiSIPC index, genotypes 10, 6, 7, and 4, based on the ssiEV index, genotypes 10, 6, 1, and 7, based on the ssiZA index, genotypes 1, 10, 6, and 7, and based on the ssiWAAS index, genotypes 1, 10, 6, and 3 were the best genotypes in terms of yield and stability. Based on the AMMI1 biplot, genotypes 1, 6, 10, and 11 with mean grain yield higher than the overall average and lowest values of IPCA1 were identified as stable genotypes with high general compatibility. In the AMMI2 biplot, genotypes 9, 11, 1, and 10 produced higher grain yields than the overall average, in addition to high general stability. In addition to the AMMI indices, Lin and Binn's superiority index was also used to identify the best genotypes, and based on this, genotypes 1, 10, 9, and 15 were the most stable genotypes in the studied environments. Using the AMMI distance parameter, genotypes 1, 3, 5, and 7 were recognized as genotypes with stable yields. Conclusion: In general, genotypes 10 (09S96510-13) and 6 (ILL2261) produced high yields in most of the environments based on different indices and showed good stability in most methods. Therefore, they could be candidates for the introduction of new cultivars.